2019
DOI: 10.1002/edn3.58
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA surveys help to identify winter hibernacula of a temperate freshwater turtle

Abstract: Background and aims Overwintering is a critical part of the annual cycle of animals living at high latitudes, and selection of overwintering sites (hibernacula) is important to population persistence. Identifying the overwintering sites of aquatic species is challenging in areas where water bodies are frozen for significant parts of the year. We tested whether environmental DNA (eDNA) approaches could help to locate them. Materials and methods We conducted environmental DNA surveys of underwater overwintering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…Environmental DNA methods have also been used to locate over-wintering sites of freshwater turtles. Feng et al [ 28 ] detected the northern map turtle eDNA from water samples collected under ice. Detections were then confirmed by visual surveys using remotely operated vehicles [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental DNA methods have also been used to locate over-wintering sites of freshwater turtles. Feng et al [ 28 ] detected the northern map turtle eDNA from water samples collected under ice. Detections were then confirmed by visual surveys using remotely operated vehicles [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al [ 28 ] detected the northern map turtle eDNA from water samples collected under ice. Detections were then confirmed by visual surveys using remotely operated vehicles [ 28 ]. Similarly, Tarof et al [ 25 ] detected eDNA of a threatened freshwater turtle at brumation sites with no previous records of species presence.…”
Section: Discussionmentioning
confidence: 99%
“…Our filtration protocol was adapted from Turner et al [ 39 ] and Feng et al [ 46 ]. We filtered water samples for environmental DNA using IsoporeTM polycarbonate tract-etched (PCTE) membrane filters (1.2-μm pore size, 47-mm diameter, from Millipore-Sigma, Oakville, ON, Canada), housed in a 47-mm in-line filter holder (Pall Corporation, Port Washington, NY, USA) and passed through with a portable peristaltic pump (Wattera, Mississauga, ON, Canada).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 12 water samples were collected from each stream (4 samples/year × 3 years = 12 samples). One liter of water was collected from the water column [13,[31][32][33] using a sterile 50-mL conical tube. At the same time, water temperature and pH were measured using a waterproof temperature/pH meter (Eutech pHTestr 30).…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…However, there is a trade-off between water volume and factors such as filtration efficiency and risk of PCR inhibition. The use of relatively small sampling volumes is common in eDNA studies, with sampling volumes of <1 L [75,76] to 1-2 L [13,[31][32][33]77]. Ma ¨chler et al [69] suggested the optimal sampling volume depends on the species-habitat combination, therefore, pilot studies are required for each study system.…”
Section: False Negativesmentioning
confidence: 99%